Influence of space–chord ratio of the airfoil cascade on the flow «choking» regimes in the blade channel - Терещенко, Юрий Матвеевич; Дорошенко, Екатерина Викторовна; Техрани, Араш (Eastern-European Journal of Enterprise Technologies, 2014)
Gas turbine engines are a major part of propulsion systems of different aircrafts. Gas-dynamic stability of compressors of aircraft GTE is achieved by using various compressor regulation methods to ensure unstalled flow of blade rows in all operation modes of the engine. The loss of gas-dynamic stability of the compressor is caused by flow separation in blade rows and critical flow regimes (flow “choking” regime) in the blade channels of separate stages. So far, flow “choking” regimes in the blade channels are not fully investigated. The effect of the cascade space–chord ratio on flow “choking” regimes in the blade channels of the airfoil cascade was studied in the paper. The authors have proposed a theoretical relationship, allowing to calculate flow “choking” regimes with different space–chord ratio of the airfoil cascade. The authors have performed a series of calculations of flow in airfoil cascades in “choking” regimes using numerical simulation. To close the averaged Navier-Stokes equations, the Menter’s SST model was used. Adaptive irregular computational grid was selected to solve this problem. For the calculation, second-order design scheme with the local use of the first-order design scheme was used. Results of studying the flow in airfoil cascades have shown a significant effect of the stall zone behind the front edge of the blades at negative angles of attack on the flow in the blade channels. Decrease in the actual minimum flow area of the blade channel leads to a reduction in the value of the Mach number Ммах, at which flow “choking” regime in the blade channels by the air consumption occurs. The results have shown that the greater the space–chord ratio of airfoil cascades, the larger the relative influence of the boundary layer thickness on the critical flow regime. Generalized characteristics of “choking” regimes of compressor cascades can be used for calculating “choking” regimes of the axial-flow compressor stages in determining the boundaries of gas-dynamic stability and “choking” boundaries of multi-stage axial-flow compressors.